Desarrollo de competencias emocionales en adolescentes pertenecientes a familias Funcionales y disfuncionales de la I.E Argemiro Escobar del Municipio de La Unión (V) (2024)
The purpose of this research project is to analyze the development of the emotional competencies of 10th Grade students of the I.E Argemiro Escobar who belong to functional families in comparison to those who are part of dysfunctional families. The theoretical approach carried out was based on the review of investigative background. Emotional competencies and their micro competencies, developmental psychology in adolescence and family. The methodology used is quantitative with a non-experimental design, since the instruments were applied at a single moment. To collect information, the family dynamics of the students were investigated through the family APGAR (Smilkstein, 1978) and the emotional competencies based on the ICEA, results that allowed us to identify that students from functional families have adequate emotional awareness and social competencies. , in response to the family support received; In contrast, young people from dysfunctional families have diminished development in most micro-competencies, except for life skills, which report optimal progress, because the absence of family support has led them to be more resourceful.